Book 4 of Afonso III: a book of inquiries? - Fontão, Diana (2025)
The trajectory of the manuscript with the shelf mark Livro 4 de Inquirições de Afonso III (Book of Inquiries 4 of Afonso III) has particularities, both at an archival level and in terms of its content, which make it stand out among the Portuguese Books of Inquiries. This article seeks to identify its journey in the Torre do Tombo Nacional Archive, looking at its inventories and its inclusion in the series to which it currently belongs. Its contents are also analyzed, in particular the documentation whose copy motivated the production of the codex: documentation relating to Portuguese Muslim communities in the 15th century. The aim is also to clarify whether this manuscript can be considered a Book of Inquiries. To this end, a brief analysis was made of the subject matter of the General Inquiries and how it was added to the codex format it currently presents. Referências bibliográficasFontesFontes manuscritas Lisboa, Arquivo Nacional da Torre do Tombo, Chancelaria Régia, Chancelaria de D. João I, livro 5. Disponível em: https://digitarq.arquivos.pt/details?id=3813668 Lisboa, Arquivo Nacional da Torre do Tombo, Contos do Reino e Casa, Núcleo Antigo 296, Tombo Geral da Índia, por Simão Botelho. Disponível em: https://digitarq.arquivos.pt/details?id=4162520 Lisboa, Arquivo Nacional da Torre do Tombo, Feitos da Coroa, Inquirições de D. Afonso III, livro 4. Disponível em: https://digitarq.arquivos.pt/details?id=4182580 Lisboa, Arquivo Nacional da Torre do Tombo, Feitos da Coroa, Inquirições de D. Dinis, livro 9. Disponível em: https://digitarq.arquivos.pt/details?id=4182571 Lisboa, Arquivo Nacional da Torre do Tombo, Gavetas, Gaveta 8, maço. 3, nº 8. Disponível em: https://digitarq.arquivos.pt/details?id=4660478 Lisboa, Arquivo Nacional da Torre do Tombo, Gavetas, Gaveta 10, maço 12, nº 17. Disponível em: https://digitarq.arquivos.pt/details?id=4185855 Lisboa, Arquivo Nacional da Torre do Tombo, Gavetas, Gaveta 15, maço. 9, nº 25. Disponível em: https://digitarq.arquivos.pt/details?id=7764298 Lisboa, Arquivo Nacional da Torre do Tombo, Leis e Ordenações, Núcleo Antigo 1, Livro de Leis e Posturas. Disponível em: https://digitarq.arquivos.pt/details?id=4223265 Porto, Biblioteca Pública Municipal do Porto, Ms. 86, pp. 389-392. Fontes impressas Portugaliae Monumenta Historica. Scriptores vol. 1, fasc. 1. Ed. Alexandre Herculano. Lisboa: Academia das Ciências de Lisboa, 1856. Disponível em: https://purl.pt/12270/4/cg-2698-a-13/cg-2698-a-13_item4/cg-2698-a-13_PDF/cg-2698-a-13_PDF_24-C-R0150/cg-2698-a-13_0000_capa-capa_t24-C-R0150.pdf Portugaliae Monumenta Historica. Leges et Consuetudines vol. 2. Ed. Alexandre Herculano. Lisboa: Academia das Ciências de Lisboa, 1868. Disponível em: https://purl.pt/12270/4/res-1795-a/res-1795-a_item4/index.html Estudos ANDRADE, Amélia Aguiar; FONTES, João Luís (eds.) – Inquirir na Idade Média: Espaços, protagonistas e poderes (sécs. XII-XIV). Tributo a Luís Krus. Lisboa: Instituto de Estudos Medievais, 2015. AZEVEDO, Pedro A. d’; BAIÃO, António — O Archivo da Torre do Tombo: sua história, corpos que o compõem e organisação. Lisboa: Annaes da Academia de Estudos Livres, 1905. BARROS, Maria Filomena Lopes de — A Comuna Muçulmana de Lisboa: sécs. XIV e XV. Lisboa: Hugin, 1998. BARROS, Maria Filomena Lopes de — “The Muslim Minority in the Portuguese Kingdom (1170-1496): identity and writing”. eJournal of Portuguese History 13/2 (2015), pp. 18-35. [Consultado a 15 de fevereiro de 2023] Disponível em: https://www.brown.edu/Departments/Portuguese_Brazilian_Studies/ejph/html/issue26/pdf/v13n2a02.pdf BARROS, Maria Filomena Lopes de — “Identificação de um país: a vivência muçulmana sob domínio cristão”. In CAETANO, Joaquim Oliveira; MACIAS, Santiago (coord.) — Guerreiros e Mártires: a cristandade e o islão na formação de Portugal. Lisboa: Imprensa Nacional-Casa da Moeda, 2020, pp. 124-131. BASTO, Artur de Magalhães — “A «Rrenembrança» dos Reis da «Torre do Tombo Real»”. In Estudos: Cronistas e crónicas antigas. Fernão Lopes e a «Crónica de 1419». Coimbra: Acta Universitatis Conimbrigensis, 1959, pp. 347-352. DINIS, António Joaquim Dias — “Relatório do século XVI sobre o Arquivo Nacional da Torre do Tombo”. Anais Academia Portuguesa da História 2ª série, 17 (1968), pp. 115-158. FONTÃO, Diana — Uma Memória Anónima: a Crónica Breve do Arquivo Nacional. Dissertação de mestrado em Estudos Medievais apresentada à Faculdade de Letras da Universidade do Porto. Porto: s.n., 2023. GOMES, Saúl António — “Inquirições, confirmações e registos da chancelaria régia portuguesa: notas para o seu estudo”. Revista de História da Sociedade e da Cultura 12 (2012), pp. 147-63. [Consultado a 16 de fevereiro de 2023] Disponível em https://ceh.fcsh.unl.pt/pdf/rev/2013/01_FRAGMENTAHISTORICA_1_SaulAntonioGomes.pdf HOMEM, Armando Luís de Carvalho — O Desembargo Régio (1320-1433). Dissertação de doutoramento em História da Idade Média apresentada à Faculdade de Letras da Universidade do Porto, 1985. Disponível em: https://repositorio-aberto.up.pt/handle/10216/13225 PESSANHA, José — “Uma reabilitação historica: inventarios da Torre do Tombo no seculo XVI”. Archivo Historico Portuguez 3 (1905), pp. 287-303. PIMENTA, Alfredo — Fontes Medievais da História de Portugal: anais e crónicas. Lisboa: Livraria Sá da Costa Editora, 1948. PIZARRO, José Augusto de Sotto Mayor — "Introdução". In PIZARRO, José Augusto de Sotto Mayor (ed.) — Portugaliae Monumenta Historica Nova Série Volume III Inquisitiones Inquirições Gerais de D. Dinis 1284. Lisboa: Academia das Ciências de Lisboa, 2007, pp. XI-XX. RAU, Virgínia — A Tôrre do Tombo em 1631. Lisboa: Bertrand, 1945. RIBEIRO, Fernanda — O Acesso à Informação nos Arquivos Parte I: o acesso à informação no quadro de desenvolvimento dos arquivos em Portugal. Dissertação de doutoramento em Arquivística apresentada à Faculdade de Letras da Universidade do Porto. Porto: s.n., 1998. Disponível em: https://repositorio-aberto.up.pt/bitstream/10216/7058/3/fribeirovol01000061435.pdf RIBEIRO, Fernanda — “Como seria a estrutura primitiva do Arquivo da Casa da Coroa (Torre do Tombo)?”. In FONSECA, Luís Adão da; AMARAL, Luís Carlos; SANTOS, Maria Fernanda Ferreira (coord.) — Os Reinos ibéricos na Idade Média: livro de homenagem ao Professor Doutor Humberto Carlos Baquero Moreno. Porto: Livraria Civilização Editora, 2003, pp. 1401-1414. RIBEIRO, João Pedro — Memórias para a História das Inquirições dos Primeiros Reinados de Portugal. Lisboa: Impressão Régia, 1815. VENTURA, Leontina; OLIVEIRA, António Resende de — “Os Livros do Rei: administração e cultura no tempo de D. Afonso III”. Boletim do Arquivo da Universidade de Coimbra 25 (2012), pp. 181-194. [Consultado a 3 de dezembro de 2023] Disponível em: https://impactum-journals.uc.pt/boletimauc/article/view/25_7/368 VILAR, Hermínia Vasconcelos — “As Inquirições no contexto do reinado de Afonso II”. In ANDRADE, Amélia Aguiar; FONTES, João Luís (eds.) — Inquirir na Idade Média: Espaços, protagonistas e poderes (sécs. XII-XIV). Tributo a Luís Krus. Lisboa: Instituto de Estudos Medievais, 2015, pp. 81-98.